Managing the cognitive loads associated with judgment and decision-making in a group of adventure sports coaches: a mixed-method investigation. Issue 1 (2nd January 2021) - Collins, Loel; Collins, Dave
ABSTRACT: This paper expands work on professional judgment and decision-making and examines the coping strategies used by adventure sports professionals to manage the cognitive loads of decision-making. Amixed methodology was employed in which asample of participants completed aPro Active Coping Inventory and asub-group then completed an Applied Cognitive Task Analysis of atypical coaching scenario. The study determines that the participants manage their cognitive load utilising arange of heuristics, avoidance strategies and instrumental support that. includes their communities of practice, anticipation of acute cognitive loads and the development of adaptable plans based on anticipated environmental conditions and client abilities. That plan is modified in response to the actual conditions and client abilities as observed. These strategies reduce the depletion of the coaches' own cognitive resources by managing the demands. We conclude that the professionals are aware of their cognitive resources and manage its expenditure.